2019
DOI: 10.1002/jctb.5920
|View full text |Cite
|
Sign up to set email alerts
|

Permeation of greywater constituents in an aquaporin based biomimetic forward osmosis membrane process: experimental performance and modeling

Abstract: BACKGROUND An aquaporin based biomimetic forward osmosis (FO) membrane was tested with 11 greywater constituents to evaluate the membrane performance. The effects of solute type and concentration on water flux and rejection were investigated. A model was developed to predict the rejection of greywater constituents in the FO process. RESULTS The aquaporin based biomimetic membrane (ABBM) presented high water flux (16.1–17.4 L m‐2 h−1) for greywater. Inorganic ions had little effect on permeability of the ABBM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…It was revealed that when the FS contains SDS, it has a negative effect on the ABM permeability since it was absorbed on the membrane surface, and the water channel of AQPs was blocked by its single molecules. [200,201] On the other hand, water permeability and salt rejection values of AQP-based hollow fiber membrane (fabricated by IP) were maintained constant after a chemical cleaning with SDS upon fouling. [39] Recently, the effect of SDS on membrane fouling was assessed, and results showed that SDS could cause reversible and irreversible fouling when it exists in the FS with sodium alginate (SA) and calcium chloride (CaCl 2 ) simultaneously.…”
Section: Cleaningmentioning
confidence: 99%
“…It was revealed that when the FS contains SDS, it has a negative effect on the ABM permeability since it was absorbed on the membrane surface, and the water channel of AQPs was blocked by its single molecules. [200,201] On the other hand, water permeability and salt rejection values of AQP-based hollow fiber membrane (fabricated by IP) were maintained constant after a chemical cleaning with SDS upon fouling. [39] Recently, the effect of SDS on membrane fouling was assessed, and results showed that SDS could cause reversible and irreversible fouling when it exists in the FS with sodium alginate (SA) and calcium chloride (CaCl 2 ) simultaneously.…”
Section: Cleaningmentioning
confidence: 99%
“…Aquaporin (AQP) membrane, a transmembrane protein with extremely high selectivity and permeability to water molecules, is fabricated by directly or indirectly embedding AQP in the organic matrix membranes (such as those for NF, RO, and FO). The selective permeability of the AQP can achieve a higher water flux and solute interception [124,125].…”
Section: Aqp Membranesmentioning
confidence: 99%